1989
DOI: 10.1016/0091-6749(89)90128-0
|View full text |Cite
|
Sign up to set email alerts
|

Dust mite allergens and asthma—A worldwide problem

Abstract: After the discovery ofhouse dust mites in 1964 their association with asthma has been reported from many different parts of the world including the developing countries. Two sets of major allergens from mites of the genus Dermatophagoides are now well recognized. The Group I allergens are glycoproteins of relative molecular mass (Mr) 25 000, which show both structural homology and cross-reactivity. The allergen Der p I has been cloned and sequenced confirming the M, and establishing its nature as a protease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
305
2
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(326 citation statements)
references
References 52 publications
13
305
2
6
Order By: Relevance
“…A recent narrative review [5] of 30 clinical trials involving bedding encasement for treating asthma found that only four of these trials reported significant reduction in dust-mite allergen exposure with concomitant reduction in bronchial hyperresponsiveness (BHR). As in many other studies [6], the review found reduction in exposure to mite allergen in ten of the studies, but BHR was not significantly reduced in asthmatic patients as compared to controls. The authors concluded that ''although bedding encasement might be an effective asthma treatment under some conditions, when implemented in clinical trials by asthma patients, its effectiveness is inconsistent and appears to be, at best, modest''.…”
Section: What's In This Issuesupporting
confidence: 55%
“…A recent narrative review [5] of 30 clinical trials involving bedding encasement for treating asthma found that only four of these trials reported significant reduction in dust-mite allergen exposure with concomitant reduction in bronchial hyperresponsiveness (BHR). As in many other studies [6], the review found reduction in exposure to mite allergen in ten of the studies, but BHR was not significantly reduced in asthmatic patients as compared to controls. The authors concluded that ''although bedding encasement might be an effective asthma treatment under some conditions, when implemented in clinical trials by asthma patients, its effectiveness is inconsistent and appears to be, at best, modest''.…”
Section: What's In This Issuesupporting
confidence: 55%
“…1 IgE antibody responses to house dust mite allergen have been considered to play an important role in the development of bronchial asthma. 2 Although, traditionally, house dust mite has been considered a perennial allergen, aggravation of clinical symptoms related to house dust mite sensitivity in association with seasonal increase in mite numbers has been frequently observed by practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore a possibility that indoor pollutants might be of greater importance in the development of asthma than outdoor pollutants. Several studies have shown significant associations between health outcomes and exposure to indoor components like environmental tobacco smoke (12)(13)(14)(15), NO2 (16), mite allergens (17)(18)(19), and mold or dampness (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%